Osteosarcomas in older adults: a report from the cooperative osteosarcoma study group - Bielack, Stefan; Lindner, Lars H.; Egerer, Gerlinde; Benzler, Katrin; Blattmann, Claudia; Grube, Matthias; Hahn, Dennis; Kager, Leo; Kühne, Thomas; Mettmann, Vanessa; Reichardt, Peter; Hecker-Nolting, Stefanie (Journal of geriatric oncology, 2023)
Osteosarcoma is typically a disease of the young, but may affect any age. Little is known about the disease in older patients beyond retirement age. We aim to describe the characteristics, treatment, and outcomes of older adult patients registered with our cooperative group.